Pelatihan Pembuatan Nata De Soya di Kelurahan Ardirejo Sebagai Pemanfaatan Limbah Cair Olahan Kedelai - Silviyanti Siswoyo, Nurul Amalia; Gema Iftitah A.Y (Jurnal Pengabdian Masyarakat, 2023)
The soybean processing industry in Indonesia is growing very rapidly. This is because tofu and tempeh products are very popular with the community. Along with the development of industry, industrial waste pollution is also unavoidable. Therefore, it is necessary to innovate the utilization of waste into products that are useful and of high value, one of which is nata de soya. Tempe home industry "Mbah So", as a tempe craftsman in RT 01 RW 01 Ardirejo is able to produce up to 80 kg of tempe per day. In addition to producing tempeh, the liquid waste produced reaches 500 liters per day. The lack of knowledge about liquid waste treatment by home industry owners causes tempeh liquid waste to be disposed of directly into the river. This causes river water pollution and creates an unpleasant odor. Mrs. PKK RT 01 RW 01 is an IRT who does not work. thus, the empowerment of women is still relatively low. Nata de soya making training is carried out using lecture methods, discussions, direct practice and mentoring. The training ran smoothly and was enthusiastically attended by partners, namely the owner of the Tempe Home Industry “Mbah So” and PKK RT 01 RW 01. The material presented included the potential and impact of liquid waste; tools, materials, and their uses; nutritional content and economic value of nata de soya; as well as the steps for making nata de soya.